Influence of Biomechanical Characteristics on Pain and Function Outcomes From Exercise in Medial Knee Osteoarthritis and Varus Malalignment: Exploratory Analyses From a Randomized Controlled Trial. Issue 9 (26th August 2015) - Bennell, Kim L.; Dobson, Fiona; Roos, Ewa M.; Skou, Søren T.; Hodges, Paul; Wrigley, Tim V.; Kyriakides, Mary; Metcalf, Ben; Hunt, Michael A.; Hinman, Rana S.
Abstract : Objective: To investigate whether selected biomechanical characteristics influence changes in pain and physical function with exercise in people with medial knee osteoarthritis (OA) and varus malalignment. Methods: We conducted post hoc exploratory analyses from a randomized controlled trial involving 100 people with medial knee OA and varus malalignment who were randomly allocated to one of two 12‐week exercise programs (quadriceps strengthening [QS] or neuromuscular exercise [NEXA]). The outcome measures were change in overall average knee pain (visual analog scale) and self‐reported physical function (Western Ontario and McMaster Universities Osteoarthritis Index). Candidate biomechanical characteristics measured at baseline were visually observed varus thrust during walking, obesity (determined by body mass index), static varus alignment, and isometric quadriceps strength. Data were analyzed with separate two‐way analyses of covariance using the interaction term of exercise group by biomechanical characteristic. Results: Ninety‐two participants were analyzed for each characteristic except varus thrust, for which 85 participants were included. For change in pain, there was a significant interaction effect between type of exercise and both varus thrust ( P  = 0.001) and obesity ( P  = 0.023). NEXA was more effective for nonobese participants (mean change 29.5 mm [95% confidence interval (95% CI) 20.5, 38.5]) and for those with varus thrust (mean change 28.7 mm [95% CI 19.4, 38.1]), whereas QS was more effective for obese people (mean change 24.7 mm [95% CI 14.9, 34.4]) and for those without varus thrust (mean change 29.4 mm [95% CI 21.2, 37.7]). Biomechanical characteristics did not influence the effect of exercise on physical function ( P > 0.05). Conclusion: These preliminary findings suggest that varus thrust and obesity influence the pain‐relieving effects of 2 different types of exercise. Further research is needed to confirm whether or not exercise that is prescribed according to specific biomechanical characteristics optimizes knee OA outcomes.